Evaluating the Performance of Foresight Studies: Evidence from the Egyptian Energy Sector - Yomna Atef Ahmed; ElHassan Anas ElSabry (Foresight and STI Governance)
Foresight projects are expected to provide realistic scenarios for different future scenarios, which provides a better information base for relevant strategies. However, these expectations often turn out to be at least difficult to fulfill due to the uncertainty of the external environment and cognitive biases. Therefore, the idea of assessing each stage of Foresight is gaining relevance, which is of particular importance in the energy sector, which affects a variety of areas of life. This article analyzes the results of the Egyptian energy foresight study, Egypt LEAPS, in terms of process efficiency and forecast accuracy as well as the factors that influenced it, including cognitive biases. The authors conclude that for each stage of foresight, a thorough analysis of weaknesses and shortcomings is necessary. Therefore, from the very beginning, the foresight process should include reliable mechanisms for assessing results and a readiness for constant iterations. Consistent process adjustments that rely on new ways of dealing with complexity and uncertainty in dealing with the future help build trust among participants and consistently reduce the level of erroneous assumptions.